Análisis de las estrategias comunicacionales utilizadas por FV Área Andina para mejorar el clima laboral, luego del informe presentado por la empresa Great Place Work y propuesta de nuevas estrategias para fortalecer la cultura corporativa de la empresa - Robles Muñoz, María Begoña (2011)
Franz Viegener is a company dedicated to manufacturing and commercialization of faucets and bathroom porcelain. It initiated in 1921 located in Argentina, where Francisco Viegener decided to create the firm FV S.A. Today the company is integrated by more than 4000 employees; it has got over 15000 retailers, 7 factories in Latin America and various commercial subsidiaries. In Ecuador, Franz Viegener operates under the trade name FV Área Andina, with an actual endowment that reaches over 1000 coworkers. FV Área Andina was submitted to two different audits between the years 2007 and 2009, the results during both years where not satisfactory enough to achieve Great Place to Works: 10 best places to work ranking in Ecuador. Therefore this proposal´s primary objective is to determine communicational strategies that will allow the company to improve its labor climate and corporative culture of such form it will be able qualify for a position in Great Place to Works ranking. The first chapter is based on Franz Viegeners history, its strategic map integrated by mission, vision and values. Continues on with its organizational structure and product commercialization; providing a clear scenario of the environment under which the investigation is developed. Chapter two is dedicated to the company Great Place to Work; its beginnings and the labor they execute in order to evaluate other enterprises, a complete description of the score parameters that are taken under consideration during the audits. Communication, labor climate and internal communications are the main topics for chapter number three. Additionally, information and communication technologies (ITCs) and corporate culture are some of the concepts within the communicational strategies for Franz Viegener will be established. The forth chapter contains the investigation done based on the surveys all the employees submitted, the SWOT analysis and recommendations that will be taken under consideration in order to present the communication plan. Finally, the communication plan will be presented, proposing new communicational strategies that will allow FV Area Andina to improve its labor climate, therefore being able to qualify in Great Place to Work ranking and accomplishing the general goal of the investigation.